First Impression in Theatrical Casting - ALDEA, Diana (Studia Universitatis Babeș-Bolyai Dramatica, 2017)
In theatre, casting is a complex process that is less frequently approached by specialized analyses, in comparison with film casting. This article seeks to emphasize the mechanisms involved in the shaping of the first impression, which matches the first chronological stage in the casting process. I will define the first impression, in the context of theatrical casting, as the manner of establishing the actor’s image following the analysis of his/her appearance and attitude – shown more or less knowingly – by a stage director, within several seconds of their first meeting. Usually, the directors’ trust in their own intuition, in the “reading” of the face, of the behavior and skills of those who appear in front of them, is absolute. But there have been quite a few cases where appearance has been contradicted by reality. On the other hand, of course, impressions cannot be shaped by the strict rules of logic, since the director is not a machine, but a human being who does not act only on rational factors, but also on affective and emotional ones. In the shaping of the first impression – a process that occurs in a limited timeframe, having a spontaneous and almost unconscious nature – an important role is played by perception, attention, observation, during which various errors of assignment may occur. All these elements turn casting into a unique event that focuses on a living, condensed and dramatic relation between the projections of two protagonists, the actor and the director, observers and observed alike[1]. [1]. Paper presented in the National Conference of Doctoral Students, organized by the Doctoral School of Theatre and Film of the “Babeș-Bolyai” University of Cluj-Napoca, 8-9 December 2016.